1980
DOI: 10.2136/sssaj1980.03615995004400030020x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration, Effectiveness, and pH Resistance of Rhizobium meliloti Populations in Oregon Soils

Abstract: The number of Rhizobium meliloti cells in the soil of alfalfa (Medicago sativa L.) fields and the effectiveness and pH resistance of strains of R. meliloti isolated from the soil were analyzed for their relationships to soil parameters. Soil samples were collected from three alfalfa‐growing areas of Oregon and analyzed for pH, exchangeable H, soil bases, P, N, and organic matter content, and cation exchange capacity. The number of infective R. meliloti cells was estimated using the plant‐infection assay. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
5

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
1
12
0
5
Order By: Relevance
“…The highest proportion of effective strains in the soils characterized by neutral pH and high content of the major nutrients (with respect to acid and poor soils) was demonstrated previously for R. leguminosarum bv. trifolii (Jones and Burrows, 1969;Masterson, 1968;Patel and Lambert, 1985) and R. meliloti (Barber, 1980).…”
Section: Increase In the Pea Yield And N Accumulation After Inoculatimentioning
confidence: 99%
“…The highest proportion of effective strains in the soils characterized by neutral pH and high content of the major nutrients (with respect to acid and poor soils) was demonstrated previously for R. leguminosarum bv. trifolii (Jones and Burrows, 1969;Masterson, 1968;Patel and Lambert, 1985) and R. meliloti (Barber, 1980).…”
Section: Increase In the Pea Yield And N Accumulation After Inoculatimentioning
confidence: 99%
“…On a 6tudid 12 souches de Rhl,zobium More recently, Munns (1965) and Barber (1980) found that some strains of R. meliLoti were more effective than others in nodulating alfalfa grown on moderately acid soils. The possibility of selecting lowpH tolerant strains of Rhizobium has often been discussed (Burton 1912Lte 1914, Munns et al .…”
mentioning
confidence: 99%
“…This behaviour might be explained by the findings of Barber (1980) who reported that the average number of R. meliloti decreased with both increasing acidity and the age of alfalfa stands.…”
Section: Resultsmentioning
confidence: 89%